1993
DOI: 10.1159/000292639
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical and Arcuate Uterine Artery Flow Velocity Measurements during Acute Hemodialysis

Abstract: Dialysis during pregnancy is a rare event associated with a poor outcome. The acute fluid volume shifts during hemodialysis are suspected to be one of the reasons for the high rate of complications during the procedure. This is the first report of uteroplacental and fetoplacental perfusion assessment during acute hemodialysis in pregnancy. The results of the Doppler measurements suggest that the maternal-fetal circulation can successfully tolerate acute volume shifts provoked by hemodialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Fetal renal intra-arterial pressure, various metabolites, and prostaglandins are among the most commonly suspected parameters that may potentially influence renal perfusion and resistance to flow. Weiner et al [4] and Jakobi et al [5] showed a reduction in the uterine and umbilical artery resistance indexes in patients undergoing hemodialysis. However, contrast to these studies, Malone et al [6] demonstrated no significant alterations in uteroplacental ratios of peak systolic blood flow velocity to diastolic veloci-ty.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Fetal renal intra-arterial pressure, various metabolites, and prostaglandins are among the most commonly suspected parameters that may potentially influence renal perfusion and resistance to flow. Weiner et al [4] and Jakobi et al [5] showed a reduction in the uterine and umbilical artery resistance indexes in patients undergoing hemodialysis. However, contrast to these studies, Malone et al [6] demonstrated no significant alterations in uteroplacental ratios of peak systolic blood flow velocity to diastolic veloci-ty.…”
Section: Discussionmentioning
confidence: 98%
“…Shifts in acute fluid volume, electrolyte imbalances, and hypotension constitute major dialysis-related complications that impair the uteroplacental circulation. The impacts of hemodialysis on the umbilical and uterine artery flow velocities were investigated only in a few cases [4][5][6]. We present the 1st case in whom the results of uteroplacental and fetal renal artery Doppler flow velocimetry performed before and after hemodialysis were evaluated concurrently with those of fetal blood sampling.…”
Section: Introductionmentioning
confidence: 99%